Phosphorylation of p90RSK is associated with increased response to neoadjuvant chemotherapy in ER-positive breast cancer - Moon Hyeong-Gon; Yi Jae; Kim Hee; Lee Hea; Lee Kyung-Min; Yi Minju; Ahn Sookyung; Shin Hee-Chul; Ju Ji-hyun; Shin Incheol; Han Wonshik; Noh Dong-Young (BMC Cancer, 2012)
Abstract Background The clinical implication of Ras/Raf/ERK pathway activity in breast cancer tissue and its association with response to chemotherapy is controversial. We aimed to explore the value of p90RSK phosphorylation, a downstram molecule of the pathway, in predicting chemotherapy response in breast cancer. Methods The expression of phosphorylated p90RSK (phospho-p90RSK) and chemotherapy response was measured in 11 breast cancer cell lines and 21 breast cancer tissues. The predictive value of phospho-p90RSK was validated in core needle biopsy specimens of 112 locally advanced breast cancer patients who received anthracycline and taxane-based neoadjuvant chemotherapy. Results In 11 breast cancer cell lines, the relative expression of phospho-p90RSK was inversely correlated with cell survival after doxorubicin treatment (p = 0.021). Similar association was observed in fresh tissues from 21 breast cancer patients in terms of clinical response. In paraffin-embedded, formalin-fixed tissues from core needle biopsy tissues from 112 patients, positive phospho-p90RSK expression was associated with greater tumor shrinkage and smaller post-chemotherapy tumor size. The association between phospho-p90RSK expression and chemotherapy response was more evident in estrogen receptor(ER)-positive tumors. The expression of phosphor-p90RSK did not show a significant relationship with the incidence of pCR. P90RSK silencing using siRNA did not affect the cancer cell’s response to doxorubicin, and the expression of phospho-p90RSK was highly correlated with other Ras/Raf/ERK pathway activation. Conclusion Our results suggest that phospho-p90RSK expression, which reflects the tumor’s Ras/Raf/ERK/p90RSK pathway activation can be a potential predictive marker for chemotherapy response in ER-positive breast cancer which needs further independent validation.